Survival of cervical cancer patients in Brunei Darussalam: 2002–2017 - Shirley HF. Lee; Nurlaylasahira Abdul Rahim; Sok King Ong; Hanif Abdul Rahman; Lin Naing (Heliyon, 2023)
Objective: Cervical cancer is the fourth leading cause of cancer deaths among Bruneian women. This study aims to investigate the survival rate of cervical cancer patients in Brunei Darussalam between 2002 and 2017, to compare survival of cervical cancer patients between two periods: 2002–2009 and 2010–2017 and to identify prognostic factors of cervical cancer. Methods: A retrospective cohort study on cervical cancer patients registered in Brunei Darussalam Cancer Registry between 2002 and 2017. De-identified data from the registry was extracted and survival analysis was performed using Kaplan-Meier estimator, log-rank test and multiple Cox regression analysis. Results: The 1-, 3- and 5-year survival rates of cervical cancer patients in Brunei Darussalam were 87.3%, 77.4% and 72.5% respectively from 2002 to 2017. The 5-year survival rate for 2002–2009 and 2010–2017 were 77.3% and 69.1% respectively. The risk of mortality was significantly higher in 2010–2017 compared to 2002–2009 after adjusting for variables (Adjusted HR = 1.59; 95% CI: 1.08, 2.40; p = 0.019). Patients with distant cancer (Adjusted HR = 11.21; 95% CI: 6.18, 20.30; p < 0.001) had the highest risk of mortality. Conclusion: The 5-year survival rate of cervical cancer patients in Brunei Darussalam was 72.5%, which ranks relatively high globally. However, increased mortality among elderly patients, and patients diagnosed with cervical cancers at the later stages, calls for public health efforts to raise awareness, early detection, and disease management.